Boundedness of p-Adic Singular Integrals and Multilinear Commutator on Morrey-Herz Spaces. (18th April 2023) - Shi, Yanlong; Li, Li; Shen, Zhonghua
Abstract : In this paper, we establish the boundedness of classical p -adic singular integrals on Morrey-Herz spaces, as well as the boundedness of multilinear commutator generated by p -adic singular integral operators and Lipschitz functions or by p -adic singular integral operators and λ -central BMO functions.